Assessment of Storage Conditions of Food items and their Relation with Food Safety in Sharm El Sheikh Resorts - Abdelrasoul, Suzan Elsayed; Kouzmal, Hany Atef (جامعة الفيوم - كلية السياحة والفنادق, 2016)
Introduction: There is no doubt that food storage is an important aspect of food hygiene not only as one of critical steps in food cycle, but also because it has become an important element of food quality in hospitality industry. The overall aim of this study is assessment of storage conditions of food items and their relation with food safety in Sharm El Sheikh Resorts in order to increase the guest safety and satisfaction.. Methodology: Both qualitative and quantitative data were collected and analyzed. Field study was accomplished through self-administered questionnaires distributed to managers in relation with food storage and observation checklist including: Safe food preparation practices (storage of hazardous food - Storage of nonhazardous food items - personal hygiene in storage places - food storage area). Results: The results showed the effect of the storage conditions on food hygiene and food quality as well as the characteristics of storage places in Sharm El Sheikh Resorts. A major contribution of this study is to improve food storage methods perfectly and food hygiene to achieve food safety for consumer satisfaction.
Keywords: المواد الغذائية -- السلامة الغذائية -- الجودة الصحية -- شرم الشيخ -- مصر